2021
DOI: 10.1002/ctm2.602
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of microRNA‐6125 promotes colorectal cancer growth through YTHDF2‐dependent recognition of N6‐methyladenosine‐modified GSK3β

Abstract: Background MicroRNAs (miRNAs), the key regulator of gene expression, and N6‐methyladenosine (m6A) RNA modification play a significant role in tumour progression. However, regulation of m6A‐modified mRNAs by miRNAs in colorectal cancer (CRC), and its effect on progression of CRC, remains to be investigated. Methods Expression of miR‐6125 and YTH Domain‐Containing Family Protein 2 (YTHDF2) was detected by western blotting and immunohistochemistry. The effects of miR‐6125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In summary, YTHDF2 may play an essential role in the prognosis of CRC. However, the protein levels of YTHDF2 were recently reported to be elevated in CRC tissues in comparison with adjacent normal tissues [ 49 ]. Overexpression of YTHDF2 facilitated the proliferation of CRC cells, suggesting that YTHDF2 may play a carcinogenic effect in CRC [ 49 ].…”
Section: Expression Pattern and Function Of Ythdf2 In Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, YTHDF2 may play an essential role in the prognosis of CRC. However, the protein levels of YTHDF2 were recently reported to be elevated in CRC tissues in comparison with adjacent normal tissues [ 49 ]. Overexpression of YTHDF2 facilitated the proliferation of CRC cells, suggesting that YTHDF2 may play a carcinogenic effect in CRC [ 49 ].…”
Section: Expression Pattern and Function Of Ythdf2 In Human Cancersmentioning
confidence: 99%
“…Glycogen synthase kinase 3 beta (GSK3β) is a crucial component of the Wnt/β-catenin pathway, and its inactivation causes β-catenin to concentrate in the cell and transfer to the nucleus to enhance the progression of tumors [ 87 , 88 ]. YTHDF2 was reported to recognize and bind m 6 A-modified GSK3β mRNA to promote its degradation, which subsequently decreased the phosphorylation of β-catenin to enhance the stability of the β-catenin protein, thereby promoting CRC cell proliferation [ 49 ]. Additionally, AXIN1, encoding a negative regulator of the Wnt/β-catenin pathway, was identified as a direct target of YTHDF2.…”
Section: Molecular Mechanisms Of Ythdf2 In Tumorigenesismentioning
confidence: 99%
“…m6A Readers, ICIs in CRC Numerous studies on m6A Reader have confirmed four genes (YTHDF1, IGF2BP1, IGF2BP1, IGFBP3, EIF3B) is a potential biomarker of CRC. It was found to downregulate YTHDF1 or IMP2, can further regulate the GLS1-glutamine metabolic axis, improve the stability of the m6A-modified GSK3b mRNA, inhibition of Wnt/-catenin/cyclin D1 expression, inhibition of CRC cell proliferation, colony formation, and increase the apoptosis levels in CRC cells, To sensitized cisplatin-resistant CRC cells (126)(127)(128).…”
Section: M6a Modification Icis In Crcmentioning
confidence: 99%
“…Therefore, this study has no practical reference value. The WNT signaling pathway plays a pivotal role in CRC, and m6A also reportedly plays a role through this pathway (67,68,92,93). Song et al (92) found that m6A is related to the occurrence of CRC, which is caused by METTL3 and related to the WNT signaling pathway.…”
Section: Crcmentioning
confidence: 99%
“…However, this study also has some shortcomings, such as a small clinical sample size and many results from a database analysis. In addition to YTHDF1, YTHDF2 also affects the growth of CRC through the Wnt/β-catenin pathway (93).…”
Section: Crcmentioning
confidence: 99%